Bacteriological profile and their antibiotic susceptibility pattern in chronic suppurative otitis media (TTD) in a tertiary care hospital - Govindaraj, Sriram; Iype, Jinu Vadakkanethu; V., Srinivasa; S., Jayendiran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic suppurative otitis media (CSOM) is one of the common infective conditions which can cause many complications if not treated properly. Improper use of antibiotic among the common population has led to many drug resistant organisms; therefore it is necessary to study the antimicrobial susceptibility pattern before treating the patient with CSOM. Aim of the study was to identify the bacterial isolates causing CSOM in tubo tympanic disease and to study their antimicrobial susceptibility pattern. Methods: The study was carried out in ENT department in Vinayaka Mission Medical College, Karaikal from July 2018 till December 2018 for six months. 60 patients of CSOM (TTD) with ear discharge attending the ENT Out Patient Department were included in the study. Swabs were collected for culture and sensitivity. Bacterial isolates were identified using standard methods and antibiotic susceptibility testing were done. Results: Pseudomonas species was the most predominant organism, which was seen in 19 patients (38%) followed by Escherichia coli (22%), Staphylococcus aureus (18%), Klebsiella species (10%). Conclusions: A continuous and periodic evaluation of microbiological pattern and their antibiotic sensitivity pattern prevalent in local area, helps in prescribe proper antibiotics for successful treatment of CSOM and thus minimizing its complications and emergence of resistant strains.